UNIVERSAL CASING OF HOLE INSTRUMENT FOR MONITORING THE GEOMECHANICAL PROCESSING - Akinin A.A. (My University, 2001)
Structure of rocks influences geomechanical processes in rock mass and determines methodology of geophysical instruments. Complex structure of the rocks leads to necessity to design multi-channel systems for monitoring the processes. Modular principle of construction of the systems should be provided. In connection with this, improved corrosion resistance, strength etc. of casing of the system are necessary. Method of protection of hole electronic instruments against external actions of aggressive medium, temperature difference, electromagnetic and acoustic disturbances has been offered. Long-term monitoring of state of rocks is provided.